2018
DOI: 10.1101/390450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Visual” Cortices of Congenitally Blind Adults Respond to Executive Demands Authors

Abstract: How functionally flexible is human cortex? In congenitally blind individuals, "visual" cortices are active during auditory and tactile tasks. The cognitive role of these responses and the underlying mechanisms remain uncertain. A dominant view is that, in blindness, "visual" cortices process information from low-level auditory and somatosensory systems. An alternative hypothesis is that higher-cognitive fronto-parietal systems take over "visual" cortices. We report that, in congenitally blind individuals, righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 126 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Actually, accumulating evidence suggests "task-switching" in the deprived primary visual cortex toward higher cognitive functions such as language, verbal and episodic memory or numerical cognition, 109e117 focused attention, 118 and executive control. 119 These results are generally described as dramatically diverging from the predictions of TSSI brain organization. This is because such functions do not typically recruit early visual areas in sighted individuals (but see 120 ), are not sensory in nature, and are not organized topographically.…”
Section: Does Tssi Organization Extend To Deprived Primary Sensory Cortices As Well?mentioning
confidence: 88%
“…Actually, accumulating evidence suggests "task-switching" in the deprived primary visual cortex toward higher cognitive functions such as language, verbal and episodic memory or numerical cognition, 109e117 focused attention, 118 and executive control. 119 These results are generally described as dramatically diverging from the predictions of TSSI brain organization. This is because such functions do not typically recruit early visual areas in sighted individuals (but see 120 ), are not sensory in nature, and are not organized topographically.…”
Section: Does Tssi Organization Extend To Deprived Primary Sensory Cortices As Well?mentioning
confidence: 88%
“…Indeed, any other result showing cross-modal recruitment of the deprived early sensory cortices, and mainly of the deprived early visual cortices, ever hinted at any preserved functional topographic maps. As a matter of fact, accumulating evidence suggests 'task-switching', in the deprived primary visual cortex, towards higher cognitive functions such as language, verbal and episodic memory or numerical cognition (Amedi et al, 2004(Amedi et al, , 2003Bedny, 2017;Bedny et al, 2011;Burton et al, 2012;Kanjlia et al, 2016;Raz et al, 2005;Röder et al, 2002;Watkins et al, 2012), focused attention (Weaver and Stevens, 2007) and executive control (Loiotile and Bedny, 2018). These results may suggest that there might be two mechanisms at place in the (re)-organization following complete visual deprivation: (a) pluripotent taskswitching plasticity taking place in deprived early visual areas, whereby these regions completely change the type of computations they respond to, thus showing their ability to process a variety of different computations -hence the pluripotency (Bedny, 2017); and (b) TSSI organization taking place in deprived higher-order visual regions, whereby these regions maintain their typical computations even if triggered by atypical sensory inputs.…”
Section: Does Tssi Organization Extend To Deprived Primary Sensory Comentioning
confidence: 99%
“…On the other hand, sensory regions, such as the auditory and visual cortices, are usually considered to preferentially process lower-level perceptual features and to contribute to the storage of representations of these features in working memory (Zanto et al, 2011;Ku et al, 2015;Christophel at al., 2017). However, the study of deafness and blindness suggests that this preference might be at least partially driven by environmental sensory experience, given that reorganisation for cognitive processing has been observed in sensory areas of deaf and blind individuals (Röder et al, 2000(Röder et al, , 2002Amedi et al, 2003Amedi et al, , 2004Buchsbaum et al, 2005;Bonino et al, 2008;Bedny et al, 2011;Park et al, 2011;Watkins et al, 2012;Ding et al, 2015;Cardin et al, 2018;Loiotile and Bedny, 2018;Rimmele et al, 2019). For example, previous studies have shown recruitment for visual working memory in the posterior superior temporal cortex (pSTC) of deaf individuals (Buchsbaum et al, 2005;Ding et al, 2015;Cardin et al, 2018), suggesting a change in function in this area from auditory to cognitive processing as a consequence of deafness.…”
Section: What Is the Role Of The Deaf Auditory Cortex In Cognition?mentioning
confidence: 99%